IMPLEMENTASI KEGIATAN MAGANG DALAM MENDUKUNG PENGELOLAAN ARSIP INAKTIF DI BPKP PERWAKILAN PROVINSI KALIMANTAN TENGAH - Arminto Arminto; Yohanes Joni Pambelum; Theresia Mentari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Inactive records management in government institutions still faces various challenges, including limited human resources, manual systems, and weak interdepartmental coordination. An internship program conducted by students at BPKP Perwakilan Provinsi Kalimantan Tengah aimed to support inactive records management through a participatory approach over four months. The methods applied included direct observation, active participation, discussions, and consultations with mentors. The results demonstrated students’ contributions in recapitulating inactive records into Microsoft Excel, labeling archives, organizing files systematically, developing the Lentera loan system based on Looker Studio, and preparing a user manual book. Challenges such as limited time and dependence on manual input were addressed through scheduled task distribution and continuous mentor guidance. The internship program proved effective in supporting inactive records governance while also providing practical experience and improving students’ competencies in archival management and public administration.